PHYSICAL THERAPY INTERVENTION IN PATIENTS WITH MAXILLARY FRACTURE: AN INTEGRATIVE REVIEW (REMUNOM, 2025)
Objective: The objective of the present study was to describe how Physiotherapeutic intervention can be effective in the rehabilitation and functional recovery of patients with maxillary trauma. Methods: This integrative review was conducted based on data collection from PubMed, Scielo, Google Scholar, and LILACS. Only systematic reviews and meta-analyses were included, excluding any other types of studies. Results: Among the four articles selected for the research, the benefits of Physiotherapy include improved functionality, accelerated healing, and pain reduction. Conclusion: Thus, it was concluded that Physiotherapy plays a significant role in improving function, reducing pain, and enhancing the quality of life in patients who have suffered facial fractures or dysfunctions, with a focus on the maxillary region. Furthermore, the scarcity of articles and studies on specific Physiotherapeutic treatment for maxillary fractures was noted.